2010
DOI: 10.1021/jo101790z
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Total Syntheses of Isodomoic Acids G and H via a Unified Strategy

Abstract: Marine neuroexcitatory compounds isodomoic acids G and H were efficiently synthesized from a common intermediate using a silicon-based cross-coupling reaction. Dividing each target compound into the core fragment and the side-chain fragment enabled the synthesis to be convergent. The trans-2,3-disubstituted pyrrolidine core fragment was accessed through a diastereoselective rhodium-catalyzed carbonylative silylcarbocyclization reaction of a vinylglycine-derived 1,6-enyne. A stereochemically divergent desilylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 136 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…The majority of work in this area has focused on hydrosilylation chemistry. Recently, a number of ruthenium catalyzed protocols have emerged for the synthesis of trisubstituted olefins using an intramolecular hydrosilylation of alkynes. These complementary routes to trisubstituted vinylsilanes are inherently limited due to the mandatory inclusion of a hydrogen atom into the product alkene. Subsequent studies on silylcarbonylation and silylcyanation of alkynes have been described to circumvent this limitation. Specifically, Ojima and Denmark have studied the silylformylation of alkynes and found that five- and six-membered rings could be formed readily in this reaction. Silylformylation and silylcyanation reactions afford the syn -alkene isomers selectively. Intermolecular versions of silylcarbocyclization reactions also afford the syn -isomers. We have recently reported that vinyl-silicon tethers can be used to control both the regio- and stereochemistry in the silylvinylation of pendent alkynes with acrylates …”
mentioning
confidence: 99%
“…The majority of work in this area has focused on hydrosilylation chemistry. Recently, a number of ruthenium catalyzed protocols have emerged for the synthesis of trisubstituted olefins using an intramolecular hydrosilylation of alkynes. These complementary routes to trisubstituted vinylsilanes are inherently limited due to the mandatory inclusion of a hydrogen atom into the product alkene. Subsequent studies on silylcarbonylation and silylcyanation of alkynes have been described to circumvent this limitation. Specifically, Ojima and Denmark have studied the silylformylation of alkynes and found that five- and six-membered rings could be formed readily in this reaction. Silylformylation and silylcyanation reactions afford the syn -alkene isomers selectively. Intermolecular versions of silylcarbocyclization reactions also afford the syn -isomers. We have recently reported that vinyl-silicon tethers can be used to control both the regio- and stereochemistry in the silylvinylation of pendent alkynes with acrylates …”
mentioning
confidence: 99%
“…Asymmetric reduction of 9 a and 9 b with [Rh(cod)( R , R )‐DiPAMP]]BF 4 (cod=1,5‐cyclooctadiene, DiPAMP=1,2‐bis[(2‐methoxyphenyl)phenylphosphino]ethane) (1 mol %) and one‐pot removal of the Cbz group with 10 % Pd/C under a hydrogen atmosphere afforded amines 11 a and 11 b . The tosylation and subsequent propargylation of the crude sulfonamides under Mitsunobu reaction conditions, as reported by Tsunoda, afforded esters 12 a and 12 b in high yields with a small optical purity loss (93 and 94 % ee , respectively) . Reduction of methyl esters with diisobutylaluminum hydride (DIBAL) at −98 °C yielded aldehydes 7 a and 7 b (Scheme ), which immediately participated in the next “anti‐Wacker”‐type cyclization without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…of TBAF•3 H 2 O as additive, in THF at room temperature: both electron rich and electron poor aryl iodides gave the coupling products in good yields (Scheme 26). More recently, the same research group applied standard silylcarbocyclization to a highly functionalized allyl propargyl amine, i.e., N-tosyl-N-methylpropargyl-(L)-vinylglycine methyl ester, as a key step for the total synthesis of isodomoic acids G and H, two kainoid amino acid derivatives isolated from red alga Chondria armata with well recognized properties as neuroexcitatory agents [78,79].…”
Section: Standard Silylcarbocyclizations Of Allyl Propargyl Ethers/am...mentioning
confidence: 99%